Perancangang E-Logbook Dinas Jaga Taruna - Muhammad Agung Raharjo; M. Akbar Kadir; Muh. Khaidir Anugrah; Rizza Nur Azizah Hardianti (Politeknik Penerbangan Makassar, 2022)
Bookkeeping of activities is very important for guard cadets, for documentation and reporting of cadet activities under the Makassar Aviation Polytechnic Cadets Character Development Center. The bookkeeping of these cadet activities is still managed conventionally, all data and information related to these activities is obtained and collected manually and by the guard cadets who are in charge of recording these activities. The goal to be achieved in this research is to make the log book of the cadet guard service from manual reports to digital reports at the Makassar Aviation Polytechnic. This type of research is Design Science Research (DSR) which aims to create new products and test them using the Black Box method by inputting valid and invalid data in order to determine deficiencies in the E-Log Book of the Makassar Aviation Polytechnic Cadres Watch Service. The test results on the Taruna Jaga E-Log Book show that inputting valid data into the cadet, class, study program, user, and picket data forms are all successful, while inputting data is invalid (random) on the cadet data form, study program, the user manages to process data which are not suitable except for the picket form which fails because it can save data.